Morchella importuna Polysaccharides Alleviate Carbon Tetrachloride-Induced Hepatic Oxidative Injury in Mice - Xu, Yingyin; Xie, Liyuan; Tang, Jie; He, Xiaolan; Zhang, Zhiyuan; Chen, Ying; Zhou, Jie; Gan, Bingcheng; Peng, Weihong (Frontiers in Physiology, 2021)
This study aimed to investigate the effects of Morchella importuna polysaccharides (MIPs) on carbon tetrachloride (CCl4)-induced hepatic damage in mice. A total of 144 female mice were randomly assigned to four treatment groups, namely, control, CCl4, low-dose MIP (LMIP) group, and high-dose MIP (HMIP) group. After the 10-day experiment, serum and liver were sampled for biochemical and metabolomic analyses. The HMIPs markedly decreased the liver weight under CCl4 intoxication. Furthermore, the significantly elevated concentrations of five serum biochemical parameters, including alanine aminotransferase, aspartate aminotransferase, triglyceride, total cholesterol, and total bile acid under CCl4 treatment were subverted by MIP administration in a dose-dependent manner. Moreover, MIPs relieved the increased hepatic malonaldehyde and protein carbonyl content and the decreased superoxide dismutase and catalase contents caused by CCl4 intoxication. There was also a dose-dependent decrease in the CCl4-induced inflammatory indices, such as the levels of interleukin-1, interleukin-6, tumor necrosis factor-alpha, and myeloperoxidase, with MIP administration. Subsequent ultra-high performance liquid chromatography–tandem mass spectrometry-based serum metabolomics identified nine metabolites between the control and CCl4 groups and 10 metabolites between the HMIP and CCl4 groups, including some critical metabolites involved in flavonoid biosynthesis, amino acid metabolism, energy metabolism, and toxicant degradation. These novel findings indicate that MIPs may be of therapeutic value in alleviating the oxidative stress and inflammation caused by CCl4. Liquid chromatography-mass spectrometry-based metabolomics provides a valuable opportunity for identifying potential biomarkers and elucidating the protective mechanisms of medicinal mushrooms against hepatic oxidative injury.